2007
DOI: 10.1017/s1751731107000456
|View full text |Cite
|
Sign up to set email alerts
|

The Asp298Asn missense mutation in the porcine melanocortin-4 receptor (MC4R) gene can be used to affect growth and carcass traits without an effect on meat quality

Abstract: A promising tool to improve daily gain in pigs is the missense mutation (Asp298Asn) in the melanocortin-4 receptor (MC4R) gene, especially in the Belgian pig industry where the slow-growing Pié train breed is very frequently used as the sire breed. The MC4R is expressed in the appetite-regulating region of the brain where it regulates feed intake and energy balance. The mutation has been associated with differences in fatness, daily gain and feed intake. However, less information on the correlated effects on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 24 publications
5
17
0
Order By: Relevance
“…Although this study did not detect a significant influence on any traits of fatness, in agreement with Park et al (2002), Meidtner et al (2006) and Van den Maagdenberg et al (2007) it can be assumed that the A allele corresponds with increased fatness. This assumption was demonstrated by several studies which indicated a significant influence of A allele on backfat thickness (Kim et al, 2000b;Hernández-Sánches et al, 2003;Houston et al, 2004;Fan et al, 2009).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Although this study did not detect a significant influence on any traits of fatness, in agreement with Park et al (2002), Meidtner et al (2006) and Van den Maagdenberg et al (2007) it can be assumed that the A allele corresponds with increased fatness. This assumption was demonstrated by several studies which indicated a significant influence of A allele on backfat thickness (Kim et al, 2000b;Hernández-Sánches et al, 2003;Houston et al, 2004;Fan et al, 2009).…”
Section: Resultssupporting
confidence: 80%
“…Several authors have reported a similar association of the Asp298Asn polymorphism of the MC4R gene with fatness and growth traits in pigs with different backgrounds (Kim et al, 2000b;Houston et al, 2004;Jokubka, 2006;Óvilo et al, 2006;Van den Maagdenberg et al, 2007;Fan et al, 2009). The authors also noted that the mutation c.746G>A of the MC4R gene is considered useful for markerassisted selection.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Moreover, significant associations were found between MC4R genotypes and backfat, growth rates and feed intake in some breeds or lines of livestock animals. A functional mutation (Asp298Asn) was associated with daily food intake, growth and fat deposition traits in some commercial pig lines (Hernandez-Sanchez et al, 2003;Houston et al, 2004;Van den Maagdenberg et al, 2007). Variants (−293C > G and −129A > G) in the 5′-untranslated region of the bovine MC4R gene were associated with two growth traits in Nanyang cattle breed (Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%